Spatial Analysis of Building Density and Liquefaction Spread in Izmit Bay and its Surroundings - Arzu Erener; Metin Aşcı; Gül Gülsoy; Aydın Üstün; Muhammed Ali Güvenaltın; Erman Şentürk; Sefa Yalvaç; Fatma Canaslan Çomut; T. Serkan Irmak; Haluk Konak; Pakize Küreç Nehbit; Efdal Kaya; et al. (Doğal Afetler ve Çevre Dergisi, 2022)
Since December 2017, with the support of Kocaeli Metropolitan Municipality and with the leadership of Kocaeli University Geomatic Department, TÜBİTAK project numbered 117Y155 and titled “Monitoring of Vertical Displacements in East Marmara (Izmit Bay) with Multi-Band InSAR and GNSS Techniques, Investigation of the Relationship Between Ground Collapse and Building Density and Liquefaction" studies have been initiated to determine the risks in the Izmit Bay area. In this context, the spatial distribution of the building density analyzes and the spatial distribution of liquefaction around the gulf region were handled and integrated in the GIS environment within the scope of the project. The spatial distributions of the building floors were examined by spatial autocorrelation studies, taking into account the 3rd dimension of the buildings for the extraction of information about the load on the ground. Among the spatial autocorrelation analysis, Local Moran’s I statistics were taken into consideration comparatively. In addition, the liquefaction potential observed around the bay and its surroundings is evaluated for 0-3 m, 3-6 m, 6-9 m, 9-12 m from 33-35 m depths. Liquefaction areas and risky areas are defined by categorizing liquefaction values for different depths according to liquefaction potential thresholds. As a result, buildings in liquefaction risk areas were determined. The study is important in terms of taking sustainable precautions against future natural disasters, preparing precaution plans for the speed and density of construction, determining the current situation of building and ground liquefaction around Gölcük and Izmit Bay, taking engineering measures in risky areas and providing building and life safety and creating a basis for disaster assessments.